Effect of Sexed and Conventional Semen on Pregnancy Rate in Murrah Buffaloes under Field Condition - Sawant, Sujata S.; Patil, Manjusha G.; Ingawale, Maheshkumar V.; Hase, Pankaj B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on twenty Murrah buffaloes selected at random from the field to evaluate the effect of sexed and conventional  semen on pregnancy rate. The buffaloes selected were initially treated with pre-synchronization medicines. The buffaloes in spontaneous  estrus with vaginal discharge and frequent micturition were divided into two groups containing ten animals. The buffaloes from group I  and II were inseminated at mid-estrus with sexed and conventional semen, respectively. The average pregnancy rate and female  calves born for AI with sex-sorted semen were 40% and 100% and for AI with conventional semen 50% and 40%, respectively. The  pregnancy rate was lower, whereas the rate of female calves born was greater after AI with sex-sorted semen than conventional  semen.
Keywords: Female calf birth; Murrah buffalo; Pregnancy rate; Sexed semen